Compress Digital Image based on Genetic Meta-Heuristic algorithm - Fawziya Ramo; Yaser Al Deen (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research a propose method has be used to compression Data of digital image  based on one of Meta Heuristic Algorithm. Genetic Meta Heuristic has been applied to obtain effective data and then performed compression operation using Vector Quantization. The proposed algorithm has been applied (we called it GMH) on sample of images.Efficince measures has been performed to calculate the value of (PSNR,MSE and correlation coefficient and compression ration). The experiments show that the proposed algorithm achives high performance and produces 87% compression rate.